PP.26.18: LONG-TERM VASCULAR SAFETY OF RENAL SYMPATHETIC DENERVATION ASSESSED BY MR IMAGING. (June 2015) - Ott, C.; Schmieder, R.S.; Lell, M.; Janka, R.; Ditting, T.; Veelken, R.; Schmieder, R.E.; Uder, M.; Schmid, A.
Abstract : Objective: Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment resistant hypertension (TRH). However, concerns have been raised regarding the long-term vascular safety after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the long-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) as well as the renal function in the long-term follow up after catheter-based RDN. Design and method: In our single-center investigator initiated study, 51 patients with true TRH (office systolic BP >  = 140/90 mmHg and 24-h ambulatory BP monitoring >  = 130/80 mmHg; at least 3 antihypertensive drugs at maximum tolerated dose including one diuretic agent) underwent catheter-based RDN using the Symplicity FlexTM catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6 – 18 months) after RDN on a 1.5T MR unit (Magnetom Avanto, Siemens Medical Solutions, Erlangen, Germany). High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiographic imaging of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated. Results: Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN all (p < 0.001). Renal function remained unchanged 6 and 12 months after RDN. In all patients MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI. Conclusions: No vascular or parenchymal complications after radiofrequency based RDN were detected in 51 patients followed up by MR imaging.